2017
DOI: 10.1007/s00441-017-2716-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of over-expression of SOD2 in bone marrow-derived mesenchymal stem cells on traumatic brain injury

Abstract: Intravenous administration of bone marrow-derived mesenchymal stem cells (BM-MSCs) has been shown to promote nerve cell regeneration following traumatic brain injury (TBI). As the anti-oxidant defense systems in neuronal tissue including superoxide dismutase 2 (SOD2) are crucial to defend cell against oxidative stress. We proposed a new stratege to increase the therapeutic effect of MSCs by preventing cells death from oxidative stress. We overexpressed SOD2 in BM-MSCs, transplanted these MSCs into TBI model mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…Unfortunately, this corroborates many other attempts with genetically modified MSCs (49,63,65,67). Studies that saw an improvement typically saw a change in only one out of multiple assessments, or only looked at a single time point (63,64,66). In one study delivering recombinant IL-4 after stroke in IL-4 knockout mice, repeated measures were not accounted for and wild-type mice were not tested (52).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Unfortunately, this corroborates many other attempts with genetically modified MSCs (49,63,65,67). Studies that saw an improvement typically saw a change in only one out of multiple assessments, or only looked at a single time point (63,64,66). In one study delivering recombinant IL-4 after stroke in IL-4 knockout mice, repeated measures were not accounted for and wild-type mice were not tested (52).…”
Section: Discussionsupporting
confidence: 56%
“…MSCs have previously been genetically altered to express desirable proteins. For rodent models of CNS injury, MSCs have been modified to overexpress bone-derived neurotrophic factor (BDNF) (63), superoxide dismutase 2 (SOD2) (64), interleukin-13 (IL-13) (65-67), or interleukin-10 (IL-10) (47,49). While most of these modifications have improved molecular parameters in each study, improved functional outcomes are only occasionally observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SOD2 is a component of antioxidant defence systems, which are crucial in defending cells against oxidative stress. SOD2-overexpressing BM-MSCs have an enhanced therapeutic effect on brain injury treatment in traumatic brain injury mice [35]. Following exposure to systemic sclerosis patient serum, MSCs enhance the expression of the SOD2 antioxidant gene to adapt to the oxidative environment and exert their therapeutic effect [36].…”
Section: Mscs Are One Of the Most Important Immunoregulatory Cell Typmentioning
confidence: 99%
“…Endotoxin found to protect MSCs and improve cell survival with increased proliferation under oxidative stress through upregulation of SOD2 [33]. Furthermore, overexpression of SOD2 in BM-MSCs found to increase its therapeutic potential in traumatic brain injury [34]. Recently, SOD3 is considered as a promising bio-compound for the treatment of several inflammatory diseases due to its ability to reduce inflammatory cascades by not only regulating oxidative stress but also by modulating various signaling pathways during inflammation.…”
mentioning
confidence: 99%